Intraoperative use of ICG fluorescence imaging to reduce the risk of anastomotic leakage in colorectal surgery: a systematic review and meta-analysis - Blanco-Colino, R.; Espin-Basany, E. (Techniques in coloproctology, 2018)
Background Indocyanine green (ICG) fluorescence imaging has been proven to be an effective tool to assess anastomotic perfusion. The aim of this systematic review and meta-analysis was to evaluate its efficacy in reducing the anastomotic leakage (AL) rate after colorectal surgery. Methods PubMed, Scopus, WOS, Google Scholar and Cochrane Library were searched up to January 2017 for studies comparing fluorescence imaging with standard care. ClinicalTrials.gov register was searched for ongoing trials. The primary outcome measure was AL rate with at least 1 month of follow-up. ROBINS-I tool was used for quality assessment. A meta-analysis with random-effects model was performed to calculate odds ratios (ORs) from the original data. Results One thousand three hundred and two patients from 5 non-randomized studies were included. Fluorescence imaging significantly reduced the AL rate in patients undergoing surgery for colorectal cancer (OR 0.34; CI 0.16–0.74; p = 0.006). Low AL rates were shown in rectal cancer surgery (ICG 1.1% vs non-ICG 6.1%; p = 0.02). There was no significant decrease in the AL rate when colorectal procedures for benign and malignant disease were combined. To date, there are no published randomized control trials (RCTs) on this subject, though 3 ongoing RCTs were identified. Conclusions ICG fluorescence imaging seems to reduce AL rates following colorectal surgery for cancer. However, the inherent bias of the non-randomized studies included, and their differences in AL definition and diagnosis could have influenced results. Large well-designed RCTs are needed to provide evidence for its routine use in colorectal surgery.